The Vocal Extent Measure: Development of a Novel Parameter in Voice Diagnostics and Initial Clinical Experience. (4th March 2018) - Caffier, Philipp P.; Möller, Andreas; Forbes, Eleanor; Müller, Constanze; Freymann, Marie-Louise; Nawka, Tadeus
Abstract : Voice range profile (VRP) and evaluation using the dysphonia severity index (DSI) represent essentials of instrument-based objective voice diagnostics and are implemented in different standardized registration programs. The respective measurement results, however, show differences. The aim of the study was to prove these differences statistically and to develop a new parameter, the Vocal Extent Measure (VEM), which is not influenced by the measurement program. VRPs of 97 subjects were recorded by two examiners using the established registration programs DiVAS (XION medical) and LingWAVES (WEVOSYS) simultaneously. The VEM was developed on the basis of VRP area and perimeter. All 194 VRP files were analyzed for various parameters and gender independence. The registration programs exhibited significant differences in several vocal parameters. A significant gender influence for DSI was found with DiVAS (p < 0.01 ), but not with LingWAVES. The VEM quantified the dynamic performance and frequency range by a unidimensional, interval-scaled value without unit, mostly between 0 and 120. This novel parameter represents an intelligible and user-friendly positive measure of vocal function, allows simple and stable VRP description, and seems to be suitable for quantification of vocal capacity. In contrast to DSI, the VEM proved to be less susceptible to registration program and gender.